Gastrointestinal T Lymphocytes Retain High Potential for Cytokine Responses but Have Severe CD4(+) T-Cell Depletion at All Stages of Simian Immunodeficiency Virus Infection Compared to Peripheral Lymphocytes - Smit-McBride, Zeljka (American Society for Microbiology, 1998)
Gastrointestinal complications in human immunodeficiency virus (HIV) infection are indicative of impaired intestinal mucosal immune system. We used simian immunodeficiency virus (SIV)-infected rhesus macaques as an animal model for HIV to determine pathogenic effects of SIV on intestinal T lymphocytes. Intestinal CD4(+) T-cell depletion and the potential for cytokine responses were examined during SIV infection and compared with results for lymphocytes from lymph nodes and blood. Flow cytometric analysis demonstrated severe depletion of CD4(+)CD8(−) single-positive T cells and CD4(+)CD8(+) double-positive T cells in intestinal lamina propria lymphocytes (LPL) and intraepithelial lymphocytes (IEL) during primary SIV infection which persisted through the entire course of SIV infection. In contrast, CD4(+) T-cell depletion was gradual in peripheral lymph nodes and blood. Flow cytometric analysis of intracellular gamma interferon (IFN-γ) and interleukin-4 (IL-4) production following short-term mitogenic activation revealed that LPL retained same or higher capacity for IFN-γ production in all stages of SIV infection compared to uninfected controls, whereas peripheral blood mononuclear cells displayed a gradual decline. The CD8(+) T cells were the major producers of IFN-γ. There was no detectable change in the frequency of IL-4-producing cells in both LPL and peripheral blood mononuclear cells. Thus, severe depletion of CD4(+) LPL and IEL in primary SIV infection accompanied by altered cytokine responses may reflect altered T-cell homeostasis in intestinal mucosa. This could be a mechanism of SIV-associated enteropathy and viral pathogenesis. Dynamic changes in intestinal T lymphocytes were not adequately represented in peripheral lymph nodes or blood.